2006
DOI: 10.2176/nmc.46.198
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Oculomotor Nerve Paresis in Anaplastic Astrocytoma With Exophytic Invasion

Abstract: Fig. 1 Photographs of ocular positions (A) andHess charts (B) showing the left oculomotor nerve paresis before the operation. AbstractA 30-year-old man presented with a supratentorial malignant glioma manifesting as isolated progressive left oculomotor nerve paresis. Computed tomography and magnetic resonance imaging showed an intra-axial tumor in the left temporal lobe, extending to the basal and prepontine cisterns, and compressing the brainstem. The tumor was removed subtotally. The histological diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The anatomical region and the cranial nerves more often affected were the cerebellopontine angle and trigeminal and vestibulocochlear nerves, while the oculomotor nerve was involved only 2 times. In most of the cases clinical symptoms related to the cranial nerve directly involved were present; only 5 cases of high-grade temporal glioma associated to isolated third cranial nerve palsy were reported in the literature [ 11 , [25] , [26] , [27] , [28] ]. We first report a case of temporo-mesial gliosarcoma, with exophytic pattern of growth to the ambient and crural cisterns and with sleeve involvement of the ipsilateral third cranial nerve, with encasement of the anterior choroidal, posterior communicant and posterior cerebral arteries, presenting without symptoms of peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical region and the cranial nerves more often affected were the cerebellopontine angle and trigeminal and vestibulocochlear nerves, while the oculomotor nerve was involved only 2 times. In most of the cases clinical symptoms related to the cranial nerve directly involved were present; only 5 cases of high-grade temporal glioma associated to isolated third cranial nerve palsy were reported in the literature [ 11 , [25] , [26] , [27] , [28] ]. We first report a case of temporo-mesial gliosarcoma, with exophytic pattern of growth to the ambient and crural cisterns and with sleeve involvement of the ipsilateral third cranial nerve, with encasement of the anterior choroidal, posterior communicant and posterior cerebral arteries, presenting without symptoms of peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The term exophytic refers to lesions that meet the following two criteria: (i) Observation in preoperative magnetic resonance imaging studies outside the anatomic limits of the brain surface and (ii) trans-surgical identification of pial and arachnoid invasion, with tumor growth through cisterns [ 5 ]. There are sporadic reports in adults about astrocytic lesions of a high degree of exophytic behavior [ 6 , 7 ], and few series of isolated cases in the pediatric population, in which their location has been infratentorial.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed only three cases of high grade gliomas presenting as complete third nerve paresis. [ 2 3 4 ] The most likely mechanism of oculomotor nerve paresis seems to be from the direct compression by the tumor. In our case, the tumor was directly compressing the third nerve and was markedly adherent to it.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature identified only three cases of gliomas presenting with isolated complete ipsilateral third nerve paresis. [ 2 3 4 ] We are reporting an unusual case of high grade glioma presenting as isolated complete third nerve paresis.…”
Section: Introductionmentioning
confidence: 99%